YIELD AND QUALITY OF AMARANTH AND WATER SPINACH AS AFFECTED BY ORGANIC FERTILIZERS AND LEGUME RESIDUES - M. A. Islam; A. N. Boyce; M. S. Azirun; M. M. Rahman; S. Afrin (Journal of Animal and Plant Sciences, 2019)
Amaranth (Amaranthus paniculatus) and water spinach (Ipomoea reptans) grown after legume residues with organic fertilizers are helpful to improve their yield and quality. Therefore, a study was carried out at the net house of the University of Malaya, Malaysia in pot assay from November 2014 to June 2015. Amaranth and water spinach were grown after yard long bean (YLB), bush bean (BB) and winged bean (WB) with VC+YLB, COM+YLB and FP+YLB; VC+BB, COM+BB and FP+BB; VC+WB, COM+WB and FP+WB treatments whereas legume was grown with VC, COM and FP treatments in complete randomized design. The highest biomass yield (889.81 g/m2) and leaf number (15.67) of amaranth was observed in VC+YLB treatment. Maximum protein content (2.16 g/100g) was observed when amaranth was grown with VC+BB. Fe, Ca and Mg content of amaranth was also higher in VC+YLB treatment. Amaranth after YLB grown with VC showed superior performance among the treatments. For water spinach, the highest biomass yield (674.69g/m2) and maximum leaf number (34.67) was observed in VC+WB treatment. Protein content of water spinach was highest (1.92 g/100g) in VC+WB treatment. Fe, Ca and Mg content in water spinach was also higher in VC+WB treatment for water spinach grown after winged bean. The biomass of bean showed a positive linear relationship with the growth and yield of amaranth and water spinach in all the treatments and rotations. The study has shown that the use of vermincompost with legume crop rotations has the potential to significantly increase yield in amaranth and water spinach.
Keywords: Amaranth; water spinach; organic fertilizers; crop rotation and legume.